Effect of different blood flow restriction training regimens combined with low-intensity training on muscle strength and cardiovascular safety in older adults: a systematic review and network meta-analysis - Ren, Meiling; Xian, Guangshen; Tan, Xiangchao; Sun, Shaocheng; Zhang, Ming (Frontiers in Physiology, 2025)
BackgroundOlder adults are experiencing a gradual decline in physical function as they age. Previous studies have shown that blood flow restriction (BFR) combined with low-intensity training can improve muscle strength and maintain cardiovascular fitness in older adults. However, it remains unclear which training regimen is the most effective. This study aims to investigate the effects of different BFR regimens combined with low-intensity training on muscle strength and cardiovascular safety in older adults.MethodPubMed, Web of Science, Embase, the Cochrane Library, Scopus, EBSCOhost, and CNKI were searched up to March 2025 to select eligible studies. The randomized controlled trials that explored the effects of BFR training on muscle strength and cardiovascular safety in older adults were included.ResultsA total of 18 studies with 626 participants were included. The results of this network meta-analysis showed that: 1) in terms of improving muscle strength: compared to the controls, low-frequency, low-pressure, and low-intensity BFR training regimen was significantly related to one-repetition maximum (1RM) strength [weighted mean difference (WMD) = 0.58, 95% CI: 0.81–1.08 P < 0.05]. Moreover, high-frequency, high-pressure, and low-intensity BFR training was associated with increased muscle cross-sectional area [WMD = 0.50,95% CI (−0.10,1.11), P > 0.05] and isometric muscle strength [WMD = 1.44,95% CI (0.75,2.12), P < 0.05]; 2) in terms of cardiovascular health: compared to the controls, BFR training regimens at different pressures and frequencies were not linked to changes in heart rate in older adults (P > 0.05). Moreover, low-frequency, low-pressure, and low-intensity BFR training regimen was associated with increased systolic blood pressure [WMD = 3.40, 95%CI (0.61,6.19), P < 0.05] and diastolic blood pressure [WMD = 13.40, 95%CI (8.96,17.84), P < 0.05] in older adults.ConclusionBased on the results, high-frequency, high-pressure, and low-intensity BFR training may serve as the optimal regimen to improve muscle strength and maintain cardiovascular fitness in older adults.Clinical Trial Registration:https://www.crd.york.ac.uk/PROSPERO/, Registration and protocol CRD42024534387.